Macro stress testing with a macroeconomic credit risk model for Finland - Kimmo Virolainen (Bank of Finland, 2004)
In the discussion paper, we employ data on industry-specific corporate sector bankruptcies over the time period from 1986 to 2003 and estimate a macroeconomic credit risk model for the Finnish corporate sector.The sample period includes a severe recession with significantly higher-than-average default rates in the early 1990s.The results suggest a significant relationship between corporate sector default rates and key macroeconomic factors including GDP, interest rates and corporate indebtedness.The estimated model is employed to analyse corporate credit risks conditional on current macroeconomic conditions.Furthermore, the paper presents some examples of applying the model to macro stress testing, ie analysing the effects of various adverse macroeconomic events on the banks credit risks stemming from the corporate sector.The results of the stress tests suggest that Finnish corporate sector credit risks are fairly limited in the current macroeconomic environment.
URN:NBN:fi:bof-20140807436
Keywords: C15; G21; G28; G33; 330; banking; credit risk; stress tests